Oil biodesulfurization: A review of applied analytical techniques - Stylianou, Marinos; Vyrides, Ioannis; Agapiou, Agapios (My University, 2021)
The wide use of fossil fuels and their associated environmental concerns, highlighted the importance of affordable and clean energy (goal 7), as adopted by the Sustainable Development Goals of the United Nations for 2030. For years now, the detection of sulfur components in liquid fuels is performed mainly for environmental and health purposes in compliance with the respective legislations. Towards this, the aerobic and anaerobic biodesulfurization (BDS) process, which entails the use of microorganisms to limit the sulfur concentration is followed. To ensure effective BDS, several traditional analytical methods are utilized, although they require bench-top, bulky, costly, and time-consuming instruments along with skilled personnel. The currently employed analytical methods are mostly chromatographic techniques (e.g. liquid and gas) coupled with various detectors. To start with, high-performance liquid chromatography with ultraviolet detector (HPLC-UV), as well as electrospray ionization-LC-mass spectrometry (ESI-LC-MS) were mostly reported. Additionally, many detectors were coupled to gas chromatography (CG) including atomic emission detector (GC-AED), flame ionization detector (GC-FID), flame photometric detector (GC-FPD), sulfur fluorescence detector (GC-SFD), mass selective detector (GC–MS), etc. The solid-phase microextraction (SPME) technique provides extra capabilities when added to the separation techniques. Towards the continuous interest in oil supercomplex synthesis, other atmospheric and surface desorption ionization techniques, as well as the multidimensional 2D chromatographic systems (GC × GC and LC × LC) were also investigated, due to their unsurpassed resolution power. The current review ends with final remarks per applied methodology and the necessity to respect and protect the human environment and life.
Keywords: Microorganisms; Bacteria; Sulfur; Fuels; Chromatography; Detectors